Production Efficiency of the Selected Agro Industries in Punjab - Khosla, Rajiv (Prabandhan: Indian Journal of Management, 2012)
Punjab agriculture has reached a stage where its viability and sustainability is in doubt. The green revolution led to a dramatic increase in agricultural production, but in the years following green revolution, high rates of productivity growth have been sustained at the cost of underground water table depletion and heavy doses of fertilizers with diminishing growth in the yields of major crops. Scholars have advocated for the development of agro-based industries in the state to offer a possible solution to the problem. However, the development of agro industries in an imprecise way will not offer any solution. The present study attempts to find out the efficient agro industries and suggests policy implications for the development of the agro based industries in the state. Notes 1. See Chadha (1999), Singh (1999), Shergill and Singh (2001), Kansra (2002), Sidhu (1999, 2002) and Singh (2004). 2. the New National Industrial Classification 1998, which is Pretty Wide-ranging, at the 5 Digit Level, has not been Found to be Comparable with the Nic 1987. Moreover, the Nic 1998 has only 16 Industries Falling under the Gamut of Agro Industries, whereas there were 45 Industries in Nic 1987.